Impact sodium salts on colloidal and rheological characteristics of nanosilica/water/electrolyte system - Andriyko, L.S.; Gun’ko, V.M.; Marynin, A.I.; Goncharuk, O.V. (Physics and Chemistry of Solid State, 2025)
The influence of sodium salts (chlorides, iodides, nitrates) on the behavior of nanosilica particles in aqueous medium was studied. The dependences of key physicochemical characteristics of the nanosilica/water/electrolyte colloidal system (zeta potential, particle size distribution, rheological characteristics) on the electrolyte and solid phase contents were determined. The zeta potential for all the systems is not below -20 V. As the salt concentration varies, there is a decrease in the ζ modulus approaching zero. It has been revealed that the adsorption and ion exchange processes due to the interaction of Na+ with a nanosilica surface can alter the system's behavior at electrolyte concentrations of 0.001-0.1 M, which manifested in the coagulation of primary nanoparticles and the peptization of agglomerates. The presence of sodium salts leads to additional structuring of the solvent and an increase in the viscosity. The highest viscosity for concentrated silica suspensions in the presence of NaI correlates to the data on an increase in the hydrodynamic radius of aggregates in low-concentration nanosilica suspensions. In the presence of sodium nitrate, silica suspensions show the lowest viscosity. In the colloidal system with nanosilica/water/electrolyte, when the solid phase concentration exceeds 7.5 wt.% and is influenced by sodium chloride and iodide, the rheopexy becomes evident after just three days of storage.